2019
DOI: 10.1111/vco.12475
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐testis antigens in canine histiocytic sarcoma and other malignancies

Abstract: Cancer‐testis antigens (CTAs) are a category of self proteins aberrantly expressed in diverse malignancies, mostly solid tumours, due to epigenetic de‐repression. Normally expressed only in fetal or gametogenic tissues, CTAs are tantalizing immunotherapy targets, since autoimmunity risks appear minimal. Few prevalent CTAs have been identified in human hematologic cancers, and just two in their veterinary counterparts. We sought to discover new CTAs in canine hematologic cancers such as histiocytic sarcoma (HS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…More recently NY‐ESO‐1 has also been detected in the vast majority of human liposarcoma samples in two distinct studies 47,48 . In canine HS and STS, Nemec and coworkers identified several putative CTs, however, none of these antigens appeared to be as promising a target as NY‐ESO‐1 is for certain human sarcomas 49 . This work highlights the potential species restrictions of CT antigens.…”
Section: Immune Effectors and The Tmementioning
confidence: 85%
See 3 more Smart Citations
“…More recently NY‐ESO‐1 has also been detected in the vast majority of human liposarcoma samples in two distinct studies 47,48 . In canine HS and STS, Nemec and coworkers identified several putative CTs, however, none of these antigens appeared to be as promising a target as NY‐ESO‐1 is for certain human sarcomas 49 . This work highlights the potential species restrictions of CT antigens.…”
Section: Immune Effectors and The Tmementioning
confidence: 85%
“…47,48 In canine HS and STS, Nemec and coworkers identified several putative CTs, however, none of these antigens appeared to be as promising a target as NY-ESO-1 is for certain human sarcomas. 49 This work highlights the potential species restrictions of CT antigens. Further, this suggests the need for ongoing screening to find candidate antigens that may be safely targeted in veterinary oncology and further prioritized for therapeutic targeting as seen in human oncology.…”
Section: Immune Effectors and The Tmementioning
confidence: 89%
See 2 more Smart Citations
“…For example, Kcnd2, Tspan12, Ing3 and Cped1 located on Chromosome six are known to promote proliferation of breast cancer cells ( Yang et al, 2023 ), be a critical factor for cancer associated fibroblast mediated invasion ( Otomo et al, 2014 ), used as a potential biomarker for CRC/breast cancer ( Kim and Lee, 2022 ; Li et al, 2023 ) or confer oncogenic effects in prostate cancer ( Zhu et al, 2023 ) respectively. Likewise on chromosome 12, expression of Matn3, Osr1, and Nt5c1b have been associated with colon adenocarcinoma, gastric and breast cancer development ( Zhao Z. et al, 2023a ; Chi et al, 2023 ; Gadwal et al, 2023 ); potential use as a biomarker for breast cancer ( Li et al, 2020 ) or promotion of EMT and metastasis in breast cancer ( Wang et al, 2020 ; Li et al, 2021 ) and identified as a cancer testis-antigen in canine malignancies ( Nemec et al, 2019 ) respectively. On the X chromosome, Il13ra1, Pgrmc1, Septin6, Ndufa1, Nkrf, Zcchc12, Lonrf3, Slc25a5, Ct47 and Dock11 have been associated with numerous cancers including: breast cancer ( Park et al, 2017 ; Zhao Y. et al, 2023 ), basal cell carcinoma ( Mamelak et al, 2005 ), glioblastoma multiforme ( Han and Puri, 2018 ), gastric cancer ( Li et al, 2019 ), hepatocellular carcinoma ( Fan et al, 2021 ), lung cancer ( Lu et al, 2023 ), neuroblastoma ( Seneviratne et al, 2023 ), osteosarcoma ( Cui and Dong, 2022 ), ovarian serous cystadenocarcinoma ( Zhang et al, 2018 ), pancreatic cancer ( Feng et al, 2021 ; Shi et al, 2022 ), papillary thyroid cancer ( Wang et al, 2017 ) and T-cell acute lymphoblastic leukemia ( Lahera et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%